LATTO-LATTO: BETWEEN GAMES TRADITIONAL AND ITS IMPACT ON STUDENTS - Maulana, Muhammad Yazid; Ibrahim, Maulana Malik; Simatupang, Surya Aldron (Proceeding International Seminar of Islamic Studies, 2023)
Lato-lato comes from the Bugis language, namely kato kato, but originated in America in the 1990s as Clankers. In this study we used a qualitative approach and interviewed children around the Helvetia field by combining the results of these interviews as in philosophical studies. In this research, there are things that distinguish it from other studies, such as what we present is the waning of the existence of lato lato in the field. This is a unique thing that makes every material there is a time and every time there is material. It's rare in 2023, we see Latto-latto's children again this is a natural thing because nothing lasts forever. Lato-lato has a tremendous impact on students both psychologically and socially. Many students do not care about the social environment because they are preoccupied with their own world.